(untitled) (The Pakistan Development Review, 2016)
This study endeavours to investigate the impact of fiscal decentralisation on the welfare concerns of poverty, and income inequality in Pakistan for the time period 1972 to 2013. In order to capture the multi-dimensional nature of fiscal decentralisation, three indicators are used namely; revenue decentralisation, expenditure decentralisation and composite decentralisation. Further, the role of institutional quality is also incorporated in apprehending the responsiveness of welfare issues towards the process of fiscal decentralisation. The estimation technique of Generalised Method of Moments (GMM) is employed for estimating the impact of fiscal decentralisation on poverty and income inequality. The empirical findings suggest that fiscal decentralisation has discretely resulted in increasing poverty and income inequality in Pakistan, but the presence of better institutional quality along with fiscal decentralisation can promise to mitigate the negative consequences of fiscal decentralisation for poverty and income inequality in Pakistan. Although, the indirect effect of fiscal decentralisation on welfare concerns, through institutional quality exhibits a fluctuating trend over time, but its average marginal effect is lower than the direct effect of fiscal decentralisation on welfare concerns. Hence, it can be perceived that the log-run welfare issues can be tackled effectively in the presence of institutional quality with a rational level of fiscal decentralisation. Also in order to reap the potential benefits of fiscal decentralisation for poverty and income inequality that has remained a catastrophe in case of Pakistan. JEL Classification: I3, 023 H53 Keywords: Fiscal Decentralisation, Welfare